Massive transfusion in children and neonates. (21st February 2013) - Diab, Yaser A.; Wong, Edward C. C.; Luban, Naomi L. C.
Summary: Resuscitation of children and neonates with severe or refractory bleeding due to surgery or trauma often requires massive transfusion (MT). Findings from recent studies have led to a better understanding of the complex pathophysiology in massive haemorrhage and the effects of MT on haemostasis. Current management of the massively bleeding adult patient has evolved over the past few decades, shifting to early transfusion of products in a balanced ratio as part of MT protocols (MTPs). Paediatric data on successful management of MT are limited and the optimal transfusion approach is currently unknown, leading to practice variability among institutions, depending on resource availability and patients' needs. Here, we review new important concepts in the biology of massive bleeding and MT, outline important management principles and current practices, and highlight available relevant adult and paediatric data.